Influence of myocardial contractility therapy for advanced heart failure - Chiriki, Dinesh; S, Arun (Eastern Journal of Medical Sciences, 2022)
With more than 5 million patients’ diagnosed with heart failure (HF) and more than 1 million hospitalizations each year, HF continues to have a significant impact on health-care resources. Despite treatment, a significant number of patients continue to have progressive HF symptoms, classified as Class III or IV. The aim of this study was to compare different inotropic therapy for patients of End-Stage Heart Failure. When persistent intravenous access was used and acute hemodynamic improvement was established, the durable medical equipment (DME) benefit category reimbursed 80% of outpatient inotropic medication and supplies for HF. Acute hemodynamic improvement was defined as a 20% reduction in pulmonary capillary wedge pressure and/or a 20% increase in cardiac index, both of which were related to a decrease in dyspnea. The Centers for Medicaid and Medicare Services contracted with regional carriers to run the program. The amounts reimbursed per beneficiary for inotrope and supplies (not adjusted for differential follow-up) were essentially representative of the inotrope cost. Dobutamine, milrinone, and supplies had mean (and median) amounts of 5025 (1168), 87781 (31440), and 7284 (3131), respectively. We found that patients who received this medication had a relatively high death rate, however not as high as people who received chemotherapy. Milrinone-treated patients were compensated more for hospitalizations both before and after starting the inotrope. In addition, the milrinone group had a higher level of digoxin use in the background. Nonetheless, there is an early decrease in overall expenditures following inotrope initiation, which can be attributed to a decrease in hospitalization. Considering the lack of double-blind trials comparing inotropes to placebo or dobutamine to milrinone, decisions regarding the use of inotropes, the type of inotrope used, and the duration of treatment should take into account the impact on resources.